Efektivitas Penerapan Model Komunikasi Pembangunan dalam Program Kampung Keluarga Berkualitas (Kampung KB) Desa Sukaharja Kabupaten Tangerang - Syafkilyana, Vika; Hanafi, Syadeli; Fauzi, Ahmad (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
This study aims to describe (1) the effectiveness of development communication in the KB village program, (2) quality family villages can change community perspectives, (3) community empowerment through the KB village program. This study uses a descriptive research method with a qualitative approach. Data collection techniques used include observation, interviews and documentation. The research data sources consist of 4 people, namely one KB Village secretary. The results of this study indicate that the KB village, 1 KB village operator and 2 active KB village participants. The results of this study indicate that the KB village is not just a development program, but also a social movement that aims to change the community's view of its role in achieving development and progress. Through active community participation, the KB village has the potential to change the village environment and build a more advanced and prosperous Indonesia.